Effect of empathy training on the empathy level of healthcare providers in Ethiopia: a cluster randomized controlled trial - Hurissa, Bekana Fekecha; Koricha, Zewdie Birhanu; Dadi, Lelisa Sena (Frontiers in Psychology, 2023)
Objective Empathy has deteriorated throughout clinical training and medical practice, and little is known about the effect of empathy training on the empathy level of healthcare providers. To address this gap, we assessed the effect of empathy training on the empathy level of healthcare providers in Ethiopia. Design A cluster randomized controlled trial study design was conducted from 20 December 2021 to 20 March 2022. The empathy training intervention was conducted for three consecutive days. Setting The study was conducted in five fistula treatment centers in Ethiopia. Participants The participants were all randomly selected healthcare providers. Main outcome measures Total mean score, percentage changes, and Cohen’s effect size were computed. A linear mixed effects model and independent t-test were used for data analysis. Results A majority of the study participants were nurses in the profession, married, and first-degree holders. There was no statistically significant difference in the baseline empathy score of the intervention arm across their socio-demographic features. At the baseline, the mean empathy scores of the control and intervention arms were 102.10 ± 15.38 and 101.13 ± 17.67, respectively. The effect of empathy training on the total mean score changes of empathy of the intervention arm compared to the control arm at each follow-up time had a statistically significant difference. After a week, a month, and three months of post-intervention, the total mean empathy scores between the intervention and control arms were as follows: (intervention 112.65 ± 18.99, control 102.85 ± 15.65, d = 0.55, p = 0.03); (intervention 109.01 ± 17.79, control 100.52 ± 12.57, d = 0.53, p = 0.034); and (intervention 106.28 ± 16.24, control 96.58 ± 14.69, d = 0.60, p = 0.016) with the overall percentage changes of 11, 8, and 5% from the baseline scores, respectively. Conclusion In this trial, the empathy training intervention was found to have more than a medium effect size. However, over the follow-up intervals, there was a decreasing trend in the total mean empathy scores of healthcare providers; suggesting that there should be continued empathy training and integration of it into educational and training curriculums to enhance and sustain the empathy of healthcare providers. Clinical Trial Registration: Pan African Clinical Trial Registry: http://www.edctp.org/panafrican-clinical-trials-registry or https://pactr.samrc.ac.za, PACTR202112564898934.